Réinventer l’art sacré: Le Groupe de Saint-Luc (1919-1945) - Noverraz, Camille (Arts du verre / Glass Art / Glaskunst, 2024)
During the first half of the 20th century, artists all over Europe investigated religious art and tried to renew its forms of expression. In Switzerland, an artistic society known as the "Groupe de Saint-Luc" was particularly influential. This book examines the identity and positioning of this group, which developed in tension with major themes, from the relationship between the Church and artists to openness to modernity in art and architecture.